Design and Implementation of the Workship Regristration Web at GBI "BETHEL AREA" Gendongan Salatiga Branch: PERANCANGAN DAN IMPLEMENTASI WEB PENDAFTARAN IBADAH DI GBI “BETHEL AREA” CABANG GENDONGAN SALATIGA - Joseph Triwin Subarjo; Mailoa, Evangs (Antivirus : Jurnal Ilmiah Teknik Informatika, 2024)
The Corona Virus pandemic has limited activities outside the community, including worship. This is related to government regulations regarding restrictions on community activities. The church was asked to limit attendance so that a system was needed that helped church administrators manage attendance. The worship registration web site is a platform created in response to the COVID-19 pandemic, which limited capacity and required the implementation of health protocols in churches. The purpose of this study is to apply a registration website that is useful for ensuring regular and safe attendance of congregations in physical worship. By registering through the website platform, churches can monitor attendance numbers, arrange congregation placement in accordance with social distancing, and ensure that all necessary health protocols can be followed properly. The study method is the Waterfall model, by using the Waterfall method in designing the registration system, the system is made much easier and more directed. The results showed that worship registration web sites became important during the COVID-19 pandemic to ensure safe and regular attendance. By using the website platform, churches can limit church capacity in accordance with health protocols, organize congregation attendance, and provide a sense of security to the congregation present. The worship registration web site is an effective tool in maintaining safety and health during worship in the midst of this pandemic. Keywords: pandemic, worship, church, website, information system The Corona Virus pandemic has limited activities outside the community, including worship. This is related to government regulations regarding restrictions on community activities. The church was asked to limit attendance so that a system was needed that helped church administrators manage attendance. The worship registration web site is a platform created in response to the COVID-19 pandemic, which limited capacity and required the implementation of health protocols in churches. The purpose of this study is to apply a registration website that is useful for ensuring regular and safe attendance of congregations in physical worship. By registering through the website platform, churches can monitor attendance numbers, arrange congregation placement in accordance with social distancing, and ensure that all necessary health protocols can be followed properly. The study method is the Waterfall model, by using the Waterfall method in designing the registration system, the system is made much easier and more directed. The results showed that worship registration web sites became important during the COVID-19 pandemic to ensure safe and regular attendance. By using the website platform, churches can limit church capacity in accordance with health protocols, organize congregation attendance, and provide a sense of security to the congregation present. The worship registration web site is an effective tool in maintaining safety and health during worship in the midst of this pandemic. Keywords: pandemic, worship, church, website, information system